Synergistic effect of Bacillus subtilis and Paecilomyces lilacinus in alleviating soil degradation and improving watermelon yield - Chen, Peng; Zhang, Jinglei; Li, Mei; Fang, Feng; Hu, Jindong; Sun, Zuowen; Zhang, Ansheng; Gao, Xingxiang; Li, Jian (Frontiers in Microbiology, 2023)
Continuous cropping of watermelon (Citrullus lanatus) may lead to soil degradation. As a soil conditioner, microbial agent has great potential in improving soil function and enhancing plant growth. In this study, we aimed to explore how microbial agent relieves the soil sickness of watermelon by analyzing watermelon performance, soil physicochemical properties and microbial community structures. Results suggested that microbial agent treatments significantly changed the photosynthetic efficiency of upper and lower leaves, which helped improve the growth of watermelon. The single fruit weight, fruit sugar degree and total phosphorus of soil following treatment with a mixture of Paecilomyces lilacinus DZ910 and Bacillus subtilis KC1723 (treatment D_K) were higher than those in single biofertilizer treatments and control. The soil microbial community under microbial agent treatments also changed significantly, indicating the feasibility of using microbial agents as soil remediations. The proportions of Pseudomonas and Flavobacterium, changed significantly after using microbial agents. Pseudomonas increased significantly after B. subtilis KC1723 and D_K treatments, while Flavobacterium increased significantly after using all three kinds of microbial agents compared to control. Increases in these bacteria were positively correlated with agronomic variables of watermelon. The fungi Aspergillus and Neocosmospora in the soil, which create an soil sickness of watermelon, decreased after KC1723 and D_K treatments. Meanwhile, Aspergillus and Neocosmospora were positively related to Myceliophthora incidence and negatively correlated with watermelon growth (single fruit weight and photosynthetic efficiency of upper leaves). Our microbial agent, especially D_K, represents a useful technique for alleviating soil sickness in watermelon.